Budaya Sekolah dalam Meneguhkan Perilaku Moderat Siswa - Abidin, Achmad Anwar (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2019)
From the results of this study, it is expected that there will be additional knowledge in the treasury of the School's religious culture that can reinforce the moderate behavior of madrasah ibtidaiyah students. This research is an ethnographic study conducted at the Al Ilahiyah Islamic Elementary School in the Rejoagung village of Ngoro District, Jombang Regency. The results of the research can illustrate the strategy of developing religious culture in the school environment, forms of school culture are developed in three levels of culture, namely the level of values, the level of practice, and the level of symbols. School culture is closely related to the perception of the values ​​that exist in schools that give birth to meaning that ultimately affects the attitudes and behavior of people in the school. These religious cultural values ​​can be seen from the ability of a person to show his own characteristics as a follower of a religion whose attitudes and behavior both physically and mentally are in accordance with the values ​​taught in a religion